Assessment of the impacts of building construction activities on the environment (2024)
Activities in building construction industry contribute to air pollution. In this study, gas data from four locations at each three building construction sites in Doha, Qatar were collected and analyzed. Questionnaires were also administered to companies that are involved in building construction projects. The results showed traces of SO2, CO2, CO and NO2 but in amounts below the detrimental limit stipulated by the Ministry of Environment, Qatar. Questionnaire responses revealed that the extraction of raw materials and the energy consumed during construction occur quite often, but strongly implicated dust generated from construction sites and waste disposal, as major factors causing air pollution in the area. It is therefore, recommended that regular monitoring of air should be carried out within building construction sites to aid detection of air contamination. This will serve as a control measure to stimulate catalytic conversion of exhaust, reuse and recycling of waste materials.